Job quality, health and productivity. An evidence-based framework for analysis - Saint-Martin, Anne; Inanc, Hande; Prinz, Christopher (Paris, 2018)
"The nature, content and milieu of work – i.e. the quality of the working environment – matter in many ways for people, firms and society as a whole. There is a great deal of evidence to show clear associations between job quality and the health of workers, their ability to successfully combine work and life while fully mobilising their skills and abilities to build a career, and their productivity. Investments in quality working environments can be welfare enhancing and economically efficient. Policies and practices reflect these findings insufficiently, an apparent paradox that finds its roots in various market failures. There is scope for public intervention to raise awareness, to ensure better coordination of key stakeholders (employers, workers’ representatives and various public entities) and to put in place the right financial incentives for firms to invest in better working conditions. Action in this field is also important in view of ongoing considerable changes in the labour market. The future of work is very uncertain at this stage; the digitalisation and uberisation of work have the potential for improvements in working conditions but also bear the risk of de-skilling, lower pay, lower job security and poor working conditions for parts of the labour force."